Imperial standard: Imperial Oil, Exxon, and the Canadian oil industry from 1880 - Graham D. Taylor (University of Calgary Press, 2019)
For over 130 years, Imperial Oil dominated Canada's oil industry. From Petrolia to Turner Valley, Imperial was always nearby and ready to take charge. Their 1947 discovery of crude oil in Leduc, Alberta transformed the industry and the country. But from 1899 onwards, two-thirds of the company was owned by an American giant, making Imperial Oil one of the largest foreign-controlled multinationals in Canada. "Imperial Standard" is the first full-scale history of Imperial Oil. It illuminates Imperial's longstanding connections to Standard Oil of New Jersey, also known as Exxon Mobil. Although this relationship was often beneficial to Imperial, allowing them access to technology and capital, it also came at a cost. During the energy crises of the 1970s and 80s, Imperial was assailed as the embodiment of foreign control of Canada's natural resources, and in the 1990s it followed Exxon's lead in resisting charges that the oil industry contributes to climate change. Graham D. Taylor draws on an extensive collection of primary sources, including both the Imperial Oil and Exxon Mobil archives, to explore the complex relationship between the two companies. This groundbreaking history provides unprecedented insight into one of Canada's most influential oil companies as well as the industry itself.
hdl:1880/110195
Keywords: 330